Classroom speech intelligibility prediction using Elman neural network - Paulraj, Murugesa Pandiyan, Prof. Madya; Sazali, Yaacob, Prof. Dr.; Ahmad Nazri, Abdullah; M., Thagirarani; M. Ridhwan, Tamjis (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/